How Does Financial‐Reporting Regulation Affect Industry‐Wide Resource Allocation? - BREUER, MATTHIAS (Journal of Accounting Research, 2021)
ABSTRACT This paper examines the impact of mandatory reporting and auditing of firms’ financial statements on industry‐wide resource allocation. Using threshold‐induced variation in the share of mandated firms in a given industry, I document that reporting mandates facilitate ownership dispersion in capital markets and spur competition in product markets. I, however, do not find that reporting mandates unambiguously improve the efficiency of industry‐wide resource allocation. With respect to auditing mandates, I find only that they impose a fixed cost on firms, deterring smaller entrants.